«Gender and political representation before and after the Great Recession, 2008-2017» - Prata; Freire, A.; Serra-Silva, S. (Political Representation and Citizenship in Portugal: from Crisis to Renewal?, 2020)
Ana Prata, André Freire and Sofia Serra-Silva (2020), « Gender and political representation before and after the Great Recession, 2008-2017», Marco Lisi, André Freire & Emmanouil Tsatsanis (editors) (2020), Political Representation and Citizenship in Portugal: from Crisis to Renewal?, Lexington Books – Rowman & Littlefield 2020.